2020
DOI: 10.3390/cancers12041021
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 is Expressed in CD34+/CD38− Stem Cells and Serves as a Potential Molecular Target in Ph-Negative Myeloproliferative Neoplasms

Abstract: Janus kinase 2 (JAK2) and signal transducer and activator of transcription-5 (STAT5) play a key role in the pathogenesis of myeloproliferative neoplasms (MPN). In most patients, JAK2 V617F or CALR mutations are found and lead to activation of various downstream signaling cascades and molecules, including STAT5. We examined the presence and distribution of phosphorylated (p) STAT5 in neoplastic cells in patients with MPN, including polycythemia vera (PV, n = 10), essential thrombocythemia (ET, n = 15) and prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 72 publications
(114 reference statements)
0
20
0
Order By: Relevance
“…Additional studies have explored the role of STATs in hematological malignancies. Phospho-STAT5 was shown to play a key role in CD34+/CD38− myeloproliferative neoplasms with downregulation by pharmacologic inhibition of JAK and STAT [24]. JAK/STAT mutations were also identified in patients with the rare and aggressive T-cell prolymphocytic leukemia (T-PLL), pointing towards a possible mode of transformation [25].…”
Section: Chapter 1: Targeting Stat3/5 In Hematopoietic Cancersmentioning
confidence: 99%
“…Additional studies have explored the role of STATs in hematological malignancies. Phospho-STAT5 was shown to play a key role in CD34+/CD38− myeloproliferative neoplasms with downregulation by pharmacologic inhibition of JAK and STAT [24]. JAK/STAT mutations were also identified in patients with the rare and aggressive T-cell prolymphocytic leukemia (T-PLL), pointing towards a possible mode of transformation [25].…”
Section: Chapter 1: Targeting Stat3/5 In Hematopoietic Cancersmentioning
confidence: 99%
“…The molecular basis of the increase in cytokine receptor expression remains unknown. Since CD25 is a STAT5-target gene in LSC 46 , 47 and STAT5 is a well-known driver in AML 48 , 49 , an attractive hypothesis would be that oncogenic signaling through STAT5 promotes expression of CD25 in post-CMML sAML LSC.…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient anti-tumor immunity is latent and anti-tumor immunotherapy is considered an effective treatment strategy for MPN [19,20]. However, PD-L1 expression was induced in the tumor by JAK2V617F mutation [4,5]. In contrast, it has been reported that T cells in peripheral blood highly express PD-1 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports on malignant tumors showed the effectiveness of immune checkpoint inhibitors [2,3]. In MPN, the Janus kinase/signal transducers and activators of transcription signaling pathway is activated via JAK2 mutation at position 617 (JAK2V617), leading to the expression of the immune checkpoint factor programmed death ligand-1 (PD-L1) [4,5].…”
Section: Introductionmentioning
confidence: 99%